Feed Conversion Efficiency, Milk Production and Methane Emission in Cows Fed Balanced Rations Containing Bypass Protein Feed - Hossain, S. A.; Sherasia, P. L.; Phondba, B. T.; Patel, B. P.; Garg, M. R. (Indian Journal of Animal Nutrition, 2017)
A field study was conducted on early lactating crossbred cows (n=27) to evaluate the effect of feeding balanced rations containing bypass protein feed on feed conversion efficiency (FCE), milk production, metabolic profile and enteric methane emission. Nutritional status of animals before feeding balanced ration was assessed by using ration balancing software developed by NDDB. Thereafter, the ration of each cow wasbalanced as per individual’s nutritional requirements and fed for 40 days. Feeding practice revealed that dietary intake of protein and energy was higher by 9.9 and 5.0%, respectively whereas calcium and phosphorus intake was lower by 33.9 and 27.0%, respectively than the requirements of cows. Balanced feeding improved (P